Comparison of Efficacy of Rosuvastatin Versus Atorvastatin in Reducing LDL Levels Among Type 2 Diabetes Mellitus Patients at a Tertiary Care Hospital - Khan, Muhammad Moeen; Iqbal, Jam Javed; Akbar, Shafiq; Ali, Hafiz Naeem; Sarwar, Noman; Ahmad, Faraz (Biological and Clinical Sciences Research Journal, 2025)
Type 2 diabetes mellitus (T2DM) is commonly accompanied by dyslipidemia, significantly increasing cardiovascular risk. Optimal lowering of low-density lipoprotein cholesterol (LDL-C) is a primary therapeutic goal. Although both rosuvastatin and atorvastatin are widely prescribed in Pakistan, comparative data regarding their LDL-lowering efficacy among local diabetic populations remain limited. Objective: To compare the efficacy of rosuvastatin versus atorvastatin in reducing LDL-C levels among patients with T2DM treated at a tertiary care hospital. Methods: A randomized controlled trial was conducted at the Department of Medicine, Medical Unit II, Sheikh Zayed Hospital, Rahim Yar Khan, from August 18, 2024, to February 18, 2025. A total of 246 patients aged 30–80 years with established T2DM and baseline LDL-C > 100 mg/dL were randomized in a 1:1 ratio to receive rosuvastatin 10 mg or atorvastatin 10 mg daily for 4 weeks. Baseline and post-treatment lipid levels were measured using standardized enzymatic assays. Efficacy was defined as achieving an LDL-C level < 100 mg/dL. Data were analyzed using SPSS version 25, with statistical significance set at p ≤ 0.05. Results: The mean age of participants was 56.4 ± 9.7 years, with 58.5% males and 41.5% females. Both groups were comparable at baseline (p > 0.05). After four weeks, rosuvastatin produced a significantly greater LDL-C reduction than atorvastatin (mean reduction: 71.9 ± 19.3 vs 57.6 ± 18.9 mg/dL, p < 0.001). Post-treatment LDL-C was considerably lower in the rosuvastatin group (92.4 ± 14.2 mg/dL) compared with the atorvastatin group (108.1 ± 17.6 mg/dL, p < 0.001). Efficacy was achieved in 79.7% of patients treated with rosuvastatin, compared with 55.3% in the atorvastatin group (χ² = 16.7, p < 0.001). Stratification by age, gender, obesity, and hypertension consistently demonstrated superior outcomes with rosuvastatin across all subgroups. Conclusion: Rosuvastatin 10 mg daily was significantly more effective than atorvastatin 10 mg in lowering LDL-C and achieving therapeutic LDL targets in patients with T2DM. Its superior efficacy across all demographic and clinical subgroups suggests that rosuvastatin may be the preferred statin for lipid control in Pakistani diabetic populations. Further long-term studies are warranted to evaluate cardiovascular outcomes associated with these differences.